2022
DOI: 10.3390/jcm11206018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periodontal Disease among Patients at the Outpatient Clinic of Internal Medicine in an Academic Hospital in The Netherlands: A Cross-Sectional Pilot Study

Abstract: There is a worldwide increase in individuals suffering ≥ 2 chronic diseases (multimorbidity), and the cause of combinations of conditions remains largely unclear. This pilot study analysed the prevalence of periodontal disease (PD) among (multi)-morbid patients at the outpatient clinic of internal medicine. PD is an inflammatory disease of the tooth supporting tissues and has a negative impact on the overall health. Data were obtained from 345 patients, on demographics, systemic conditions and presence of PD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“… 5 , 6 , 7 Previous research has shown the role of stress hormones on growth of selected periodontitis-related bacteria, 6 and evidence shows that NO deficiency at the endothelial level may be associated with the development of hypertension and other forms of cardiovascular disease. 7 Moreover, periodontal and cardiovascular diseases have been linked, 8 , 9 , 10 , 11 which preempts a hypothesis of a linkage amongst stress, periodontal disease, oral microbiota, and systemic homeostasis. According to different authors, academic stress is an important psychosocial challenge for both students and undergraduates, 12 and the role of academic stress has already been studied with regards to oral NO levels.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 Previous research has shown the role of stress hormones on growth of selected periodontitis-related bacteria, 6 and evidence shows that NO deficiency at the endothelial level may be associated with the development of hypertension and other forms of cardiovascular disease. 7 Moreover, periodontal and cardiovascular diseases have been linked, 8 , 9 , 10 , 11 which preempts a hypothesis of a linkage amongst stress, periodontal disease, oral microbiota, and systemic homeostasis. According to different authors, academic stress is an important psychosocial challenge for both students and undergraduates, 12 and the role of academic stress has already been studied with regards to oral NO levels.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco, alcohol, medications, uncontrolled diabetes and obesity have been suggested as factors that should be taken into consideration for a personalized care model for the management of periodontal diseases [13]. In a cross-sectional pilot study from the Netherlands, periodontal disease was highly prevalent in multimorbidity patients, and significant associations were found in patients with cardiovascular diseases [14]. Systemic inflammatory conditions including hypertension, arthritis, asthma, diabetes and HIV were also found to be significantly associated with the severity of bone loss as well as diabetes, lupus and the extent of missing teeth in a retrospective study that included 4890 randomly selected patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Severe PD is recognized as the primary cause of extensive tooth loss and complete toothlessness (edentulism) among adults worldwide 3) . PD has been reported to be associated with atherosclerotic cardiovascular (ASCV) diseases, such as acute myocardial infarction (AMI) 4) and ischemic stroke 5) . In patients with PD, they had higher values of low-density lipoprotein (LDL) cholesterol and high-sensitivity Creactive protein 6) .…”
Section: Introductionmentioning
confidence: 99%